2022
DOI: 10.3390/nu14132616
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Dietary Intake and Eating Behaviors for People with Serious Mental Illness: A Qualitative Study

Abstract: The impact of poor diet quality and nutritional inadequacies on mental health and mental illness has recently gained considerable attention in science. As the opinions and experiences of people living with serious mental illness on dietary issues are unknown, we aimed to understand the role of nutrition in a biopsychosocial approach. In total, 28 semi-structured interviews were conducted with people living with serious mental illness (SMI) in Australia, Germany and Austria, and a generic thematic analysis appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
(81 reference statements)
1
3
0
3
Order By: Relevance
“…The guilt brought by eating may lead to an increase in individual shame and further cause the depressive symptom of Anhedonia, which is a negative effect of diet on the body and mind or a mental burden [ 64 , 65 ]. Mueller-Stierlin's study suggested that negative effects such as guilt were most important for patients [ 66 ]. Guilty is a sign of low self-esteem and low self-confidence about one's own behaviour, which is consistent with Smith's study, which suggested that self-esteem, lack of energy, and feeling overwhelmed linked ED with depression and anxiety symptoms, with self-esteem being the basis for comorbidity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guilt brought by eating may lead to an increase in individual shame and further cause the depressive symptom of Anhedonia, which is a negative effect of diet on the body and mind or a mental burden [ 64 , 65 ]. Mueller-Stierlin's study suggested that negative effects such as guilt were most important for patients [ 66 ]. Guilty is a sign of low self-esteem and low self-confidence about one's own behaviour, which is consistent with Smith's study, which suggested that self-esteem, lack of energy, and feeling overwhelmed linked ED with depression and anxiety symptoms, with self-esteem being the basis for comorbidity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Det er velkjent blant psykiatrisk helsepersonell at atypiske antipsykotiske legemidler som olanzapin og klozapin fører til kraftig vektoppgang (4). I tillegg har pasienter med en alvorlig psykisk lidelse ofte usunne kostvaner (13). At dette passerer som et akseptabelt faktum, er problematisk når man tar den økte dødeligheten fra kardiovaskulaer sykdom i betraktning.…”
Section: Bivirkninger Av Antipsykotikaunclassified
“…Es wurde eine exploratorische, qualitative Studie mittels leitfadengestützten Interviews mit Personen mit psychischen Erkrankungen aus Deutschland, Österreich und Australien durchgeführt. Im Rahmen dieser Studie wurden bereits die subjektiven Determinanten des Ernährungsverhaltens [28] und dessen Implikationen [29] bei Menschen mit psychischen Erkrankungen untersucht. Aufgrund des räumlichen Bezuges der Fragestellung wurden die Interviews aus Australien aus der vorliegenden Analyse ausgeschlossen.…”
Section: Studiendesignunclassified
“…fehlende Unterstützung bei den Betroffenen zu Hoffnungslosigkeit und Resignation führt. Die Betroffenen berichteten in diesem Zusammenhang auch davon, dass das Thema Ernährung bei ihnen negative Emotionen hervorrufe, wobei Schuldgefühle und Stigmatisierung eine große Rolle spielen [29]. Ernährungsbezogene Interventionen sind somit nicht nur wichtig zur Aufrechterhaltung bzw.…”
Section: Diskussionunclassified